The Syndemic Condition of Psychosocial Problems and HIV Risk Among Male Sex Workers in Ho Chi Minh City, Vietnam - Biello, Katie (AIDS Behav, 2014)
In Vietnam, the co-occurrence (i.e., “syndemic”) of psychosocial factors (e.g., depression and substance use) may disproportionately burden male sex workers and increase their HIV risk. A comprehensive survey was conducted among 300 male sex workers in Ho Chi Minh City, Vietnam in 2010. We performed logistic regression to examine the association between the syndemic variable – a count score of the number of 5 psychosocial conditions endorsed – and unprotected anal sex (UAS) in the past. One-third of participants reported any UAS, and 42% reported ≥ 2 psychosocial health problems. In multivariable models, experiencing ≥ 4 psychosocial health problems was significantly associated with UAS. Every unit increase in number of psychosocial health problems was associated with a 25%–30% increase in odds of UAS. Understanding the syndemic condition and its association with HIV risk among male sex workers in Vietnam may lead to the development of more effective, comprehensive interventions.